2018
DOI: 10.1002/ehf2.12315
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the randomized multicentre His Optimized Pacing Evaluated for Heart Failure (HOPE‐HF) trial

Abstract: AimsIn patients with heart failure and a pathologically prolonged PR interval, left ventricular (LV) filling can be improved by shortening atrioventricular delay using His‐bundle pacing. His‐bundle pacing delivers physiological ventricular activation and has been shown to improve acute haemodynamic function in this group of patients.In the HOPE‐HF (His Optimized Pacing Evaluated for Heart Failure) trial, we are investigating whether these acute haemodynamic improvements translate into improvements in exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Baseline patient demographics together with relevant clinical information (QRS duration, NYHA class, LV function, presence of IHD) were recorded. Patients identified as being recruited into blinded randomized controlled trials, including the HOPE-HF double-blind randomized crossover trial, 7 were excluded from this analysis. Where patients were noted to have multiple indications, only one was recorded-this was the one with the strongest pacing indication.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline patient demographics together with relevant clinical information (QRS duration, NYHA class, LV function, presence of IHD) were recorded. Patients identified as being recruited into blinded randomized controlled trials, including the HOPE-HF double-blind randomized crossover trial, 7 were excluded from this analysis. Where patients were noted to have multiple indications, only one was recorded-this was the one with the strongest pacing indication.…”
Section: Methodsmentioning
confidence: 99%
“…HBP can preserve physiological activation in patients with an intact conduction system and even can correct bundle branch block (BBB) to restore normal ventricular activation. [2][3][4][5][6] The electrocardiogram (ECG) is a key tool for identifying successful pacing. Conventional ventricular pacing produces characteristic, easily discernible changes in the 12-lead ECG.…”
Section: Introductionmentioning
confidence: 99%
“…One acute hemodynamic study showed that AV‐optimized HBP could improve systolic heart function in these patients, similar to the improvement from biventricular pacing . The His Optimized Pacing Evaluated for Heart Failure (HOPE‐HF) trial that is also expected to end in 2019 is a randomized crossover study of 160 patients that aims to evaluate the performance of HBP on patients with long PR interval (over 200 ms), LVEF less than 40%, and either narrow QRS (≤140 ms) or right bundle branch block …”
Section: Discussionmentioning
confidence: 99%
“…22 The His Optimized Pacing Evaluated for Heart Failure (HOPE-HF) trial that is also expected to end in 2019 is a randomized crossover study of 160 patients that aims to evaluate the performance of HBP on patients with long PR interval (over 200 ms), LVEF less than 40%, and either narrow QRS (≤140 ms) or right bundle branch block. 23 As a result, the His bundle is an ideal site for physiological pacing because of the engagement of the normal stimulation through the His-Purkinje conduction system. For heart failure patients, HBP could achieve cardiac resynchronization by correcting left bundle branch block (LBBB) via pacing the His-Purkinje system.…”
Section: Discussionmentioning
confidence: 99%